The Effect of Therapeutic Group Therapy on Improving Students' Self-Concept VII Madrasah Tsanawiyah Private Islamiyah City North Sumatran Areca 2021 - Yetti Fauziah; Muhammad Ali Murdana Siregar (Institute of Computer Science (IOCS), 2021)
Self-concept is a holistic view of himself, which includes his abilities, feelings he experiences, his physical condition and his immediate environment. Negative self-concept is triggered by several things, ranging from the inability to respect oneself to the inability to play a role in the family environment and friends around it. One of the ages at risk for developing a negative self-concept is teenagers. One way to change adolescent self-concept from Negative to Positive is by Therapeutic Group Therapy. Group therapy is an important place for social learning because social interaction is a key aspect of the adolescent development process. This study aims to determine the effect of Therapeutic Group Therapy on improving the self-concept of the VII private Madrasah Tsanawiyah students in the city of Pinang Utara, North Sumatra in 2021. This study used a pre-experimental type with a one group pretest and posttest design. The number of the research population was 150 people from several seventh grade students who had negative self-concepts. The number of samples is 16 people, using the Non Probability technique, the instrument used is the TSCS Questionnaire whose validity has been tested by previous researchers. The results of the study using the Paired T Test obtained p value 0.000 (p <0.05). This shows that there is an effect of Therapeutic Group Therapy on the Improvement of Student Self-Concept VII Madrasah Tsanawiyah Private Islamiyah City of Pinang, North Sumatra in 2021.